2010
DOI: 10.1002/mpr.325
|View full text |Cite
|
Sign up to set email alerts
|

The Self‐Stigma of Depression Scale (SSDS): development and psychometric evaluation of a new instrument

Abstract: Self-stigma may feature strongly and be detrimental for people with depression, but the understanding of its nature and prevalence is limited by the lack of psychometrically-validated measures. This study aimed to develop and validate a measure of self-stigma about depression. Items assessing self-stigma were developed from focus group discussions, and were tested and refined over three studies using surveys of 408 university students, 330 members of a depression Internet network, and 1312 members of the gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
81
0
25

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(110 citation statements)
references
References 42 publications
4
81
0
25
Order By: Relevance
“…      Depression Self Stigma Scale (DSSS) [133] 32 items measuring self-stigma related to depression.      Self Stigma Depression Scale (SSDS) [134] 16 items assessing levels of measures shame, selfblame, help-seeking inhibition and social      inadequacy regarding depressive symptoms.…”
Section: Coping Resourcesmentioning
confidence: 99%
“…      Depression Self Stigma Scale (DSSS) [133] 32 items measuring self-stigma related to depression.      Self Stigma Depression Scale (SSDS) [134] 16 items assessing levels of measures shame, selfblame, help-seeking inhibition and social      inadequacy regarding depressive symptoms.…”
Section: Coping Resourcesmentioning
confidence: 99%
“…Two scales have been specifically developed for selfstigma in people with depression -the Depression Self-Stigma Scale (DSSS) by Kanter, Rusch, and Brondino (2008) and the Self-Stigma of Depression Scale (SSDS) by Barney, Griffiths, Christensen, and Jorm (2010 as mentioned earlier, has shown that personal self-stigma has more impact on a person with depression than anticipated stigma from others. Stevelink et al (2012) .…”
Section: Self-stigma Measurementsmentioning
confidence: 99%
“…While the SSDS's limited reliability is admittedly a constraint, I chose to use it for the reasons detailed in the previous paragraph and also because it was developed in an Australian context (Barney et al, 2010). To counter the limitations of the SSDS, I combined items from it with the ISMI (modified to be relevant to depression).…”
Section: Self-stigma Measurementsmentioning
confidence: 99%
See 2 more Smart Citations